Nosocomial septicemia in neonates - Rachma F. Boedjang (Paediatrica Indonesiana, 1999)
This study reports the prevalence of nosocomial septicemia (NS) and the relative risk (RR) of NS in neonates with intravenous (IV) line as well as in low birth weight infant, and the role of C-reactive protein (CRP) in detecting septisemia. We evaluated a prospective cohort of 182 out of 541 neonates admitted to the Special Care Unit of Cipto Mangunkusumo General Hospital, Jakarta, during a 12 months period (October 1996 to September 1997). Information was recorded on each baby's indentity including primary diagnosis. On the basis of clinical evidence they were divided into two groups: neonates with IV line (92) and non IV line (90). Neonates in whom clinical was suspected when they were more than 72 hours of admittance were eligible for study. Clinical diagnosis of septicemia was confirmed by CRP and proven by blood culture. There were 182 newborn infants, 106 boys of them were boys. 66 out of 182 (36.3%) were diagnosed as septicemia clinically. Among them (81.8%) were CRP positive and 85.2% were proven by blood culture. The overall prevalence of septicemia was 25.3% of evaluation and was most common in IV line with a prevalence of 36.9%, while in non IV line was 13.3%. The RR of NS in IV line and low birth weight infants were 2,74 and 2.67 respectively. The etiologic agents were mostly gram negative: E. coli (49.1%), Pseudomonas sp. (16.4%), Enlorobacter sp. (19.1%). The only gram positive cocci was Staphylococcus aureus (12.7%). NS almost always occurs in Special Care Unit. CRP was a valuable adjunct for diagnosing septicemia. The RR was higher in IV line and low birth weight infants. The most common pathogens in this study was gram negative.